2007
DOI: 10.1180/minmag.2007.071.2.155
|View full text |Cite
|
Sign up to set email alerts
|

LREE distribution patterns in zoned alkali feldspar megacrysts from the Karkonosze pluton, Bohemian Massif - implications for parental magma composition

Abstract: The elemental compositions of zoned alkali feldspar megacrysts from the Karkonosze pluton have been analysed and Pb isotope ratios determined using LA-ICP-MS, EMPA and TIMS. The results are used to interpret the magmatic environments within which they crystallized. Growth zones in the megacrysts show fluctuating trace element patterns that reflect a systematic relationship between incompatible LREE and compatible Ba. Chemical gradients between zones in the cores and rims of the megacrysts are not accompanied b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 52 publications
(98 reference statements)
3
18
1
Order By: Relevance
“…The Pb isotope signatures of the megacrysts are consistent with mixing between a mantle and a crustal endmember (Słaby et al 2007b). Using the Kober and Lippolt (1985) model for crust-mantle Pb isotope evolution, the amount of mantle-derived Pb in the feldspar composition can be estimated as 20-40% (Słaby et al 2007b).…”
Section: Basic Principlesmentioning
confidence: 83%
See 3 more Smart Citations
“…The Pb isotope signatures of the megacrysts are consistent with mixing between a mantle and a crustal endmember (Słaby et al 2007b). Using the Kober and Lippolt (1985) model for crust-mantle Pb isotope evolution, the amount of mantle-derived Pb in the feldspar composition can be estimated as 20-40% (Słaby et al 2007b).…”
Section: Basic Principlesmentioning
confidence: 83%
“…If growth was driven by kinetically controlled processes, the uptake of compatible elements would have been decoupled from that of the incompatible elements (Morgan and London 2003). Some of the zones appear to have crystallized in a homogenous magmatic environment having clear geochemical affinities with the end-member magmas in the Karkonosze pluton (Słaby et al 2007b), whereas others crystallized in heterogeneous domains of hybridized magma. Geochemical modeling of megacryst growth revealed that zones that can be related to almost pure mafic end-member magma are rare and their width extremely narrow (Słaby et al 2007a).…”
Section: Basic Principlesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this method is of lower sensitivity and is usable only for an approximate assessment of crystal composition heterogeneity. The depiction of the crystal geochemical data obtained from measurements along a traverse consists of a Cartesian diagram that includes two variables: location of the measurement points along the traverse and the corresponding element concentration (Gagnevin et al 2005a;Ginibre et al 2002;Ginibre et al 2004;Słaby et al 2007a;Słaby et al 2007b). This methodology exhibits, only to a certain extent, the complexity of crystallisation process in a heterogeneous magmatic mass created by contamination, magma mixing and crystallization.…”
Section: Introductionmentioning
confidence: 99%